Real-time liver uptake and biodistribution of magnetic nanoparticles determined by AC biosusceptometry - Quini, Caio C. [UNESP]; Prospero, Andre G. [UNESP]; Calabresi, Marcos F. F. [UNESP]; Moretto, Gustavo M. [UNESP]; Zufelato, Nicholas; Krishnan, Sunil; Pina, Diana R. [UNESP]; Oliveira, Ricardo B.; Baffa, Oswaldo; Bakuzis, Andris F.; Miranda, Jose R. A. [UNESP] (Elsevier B.V., 2017)
We describe the development of a joint in vivo/ex vivo protocol to monitor magnetic nanoparticles in animal models. Alternating current biosusceptometry (ACB) enables the assessment of magnetic nanoparticle accumulation, followed by quantitative analysis of concentrations in organs of interest. We present a study of real-time liver accumulation, followed by the assessment of sequential biodistribution using the same technique. For quantification, we validated our results by comparing all of the data with electron spin resonance (ESR). The ACB had viable temporal resolution and accuracy to differentiate temporal parameters of liver accumulation, caused by vasculature extravasation and macrophages action. The biodistribution experiment showed different uptake profiles for different doses and injection protocols. Comparisons with the ESR system indicated a correlation index of 0.993. We present the ACB system as an accessible and versatile tool to monitor magnetic nanoparticles, allowing in vivo and real-time evaluations of distribution and quantitative assessments of particle concentrations. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: AC biosusceptometry; Magnetic nanoparticles; Biomedical instruments; Real time monitoring; Quantification methods; Nanoparticle uptake